(untitled) (Dhaka University Journal of Applied Science and Engineering, 2023)
High throughput plant phenotyping is the advanced scientific approach for rapid phenotyping of plant traits, especially high consumable grains or crops, which is designed to process a high volume of data in a short time for plant breeders and cultivars to utilize. Detection and counting of crop traits such as plants, fruits, wheat or rice spikes, sorghum head, and plant diseases is more advanced research in this field, where real-world data are collected using aerial and land-based imaging platforms equipped with a variety of geospatial sensors, and their statistical analysis is conducted using Artificial Intelligence (AI) and Deep Learning-based solutions. In this paper, we contributed to solving such a challenge of phenotyping by detecting and counting wheat spikes from land-based imaging by applying a Region-based Convolutional Neural Network (CNN) model. Our method employs the use of CNN to extract features from the imaging platform and the learning model is trained to detect and count wheat spikes in field images based on these extracted features. Using the publicly available SPIKE dataset to train and test our model, our proposed method achieved 98% average precision and 91% average F1 score on the test set. Our results show a significant improvement of 2.9% and 11.2% in detection accuracy as well as 1% and 3% in average precision metric over state-of-the-art Faster Regionbased Convolutional Neural Network (Faster-RCNN), and RetinaNet, respectively, and have the potential to significantly benefit plant breeders by facilitating the selection of wheat varieties with high yields. DUJASE Vol. 7 (2) 21-30, 2022 (July)